PERBANYAKAN TANAMAN PASAK BUMI (Eurycoma longifolia Jack) SECARA GENERATIF DAN VEGETATIF DI PERSEMAIAN - Fitriani, Sri; Astiani, Dwi; Wahdina, . (Universitas Tanjungpura, 2017)
Pasak bumi (Eurycoma longifolia Jack) is a native plant to Indonesia which has many properties and benefits. Howevel the population in the natural forest is increasingly rare due to excessive exploitation. Pasak bumi has recalcitrant seeds type phenological conditions it is a monopodial type plant so that its multiplication can be produced vegetatively by stem cutting. This research aimed to get the suitable method for pasak bumi plant propagation. This study an experimental method by comparing generative with seeds and stump method and used vegetative cuttings. Seed germinated an moss began on day 12 th with a percentage of 38,84%, whereas on sand media did not germinate at all. Stump survival percentage was 84,5%, new shoots grow out after 1 month after planting. The growing percentage of cuttings was 20,8%. Both seedling stump and cutting were growing sprout from the shoots and was stems, with a varying number of buds. Environmental conditions such as air temperature, humidity, and light intensity affected the processes of the pasak bumi propagation. Keywords : generative propagation, pasak bumi, seedlings, vegetative propagation.